Stres Akademik sebagai Faktor Risiko Dispepsia Fungsional pada Mahasiswa Preklinik Fakultas Kedokteran Universitas Hang Tuah : Academic Stress as a Risk Factor for Functional Dyspepsia among Preclinical Medical Students at Hang Tuah University - Naufal Waly Anas; M. Fathi Ilmawan; Peppy Nawangsasi; I Ketut Tirka Nandaka (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2026)
Medical education is widely recognized for its high academic demands, intensive schedules, and frequent examinations, all of which may contribute to academic stress among students. Unmanaged stress can affect the autonomic nervous system and increase gastric acid secretion through interactions within the brain–gut axis, manifesting as gastrointestinal disturbances, particularly functional dyspepsia. This study aimed to examine the relationship between academic stress and the occurrence of functional dyspepsia among preclinical medical students of the Faculty of Medicine, Hang Tuah University, class of 2022. This study employed an descriptive correlational design with a cross-sectional approach. The sampling technique used was purposive sampling, involving 72 students selected from the 2022 cohort population. Data were collected using PSS-10 to assess stress levels and R4-FDDQ to diagnose functional dyspepsia. Data analysis was conducted using the Chi-square statistical test. The results demonstrated a statistically significant association between academic stress and functional dyspepsia, as indicated by the Chi-square test with a p-value of 0,014. This study concludes that there is a significant relationship between academic stress and the occurrence of functional dyspepsia among preclinical medical students of the Faculty of Medicine, Hang Tuah University, class of 2022. Higher levels of academic stress are associated with an increased likelihood of developing functional dyspepsia. ABSTRAK Pendidikan kedokteran dikenal memiliki tuntutan akademik yang tinggi, padatnya jadwal, dan ujian yang sering, yang berpotensi memicu stres akademik pada mahasiswa. Stres yang tidak tertangani dapat memengaruhi sistem saraf otonom dan meningkatkan sekresi asam lambung melalui interaksi brain-gut axis, yang bermanifestasi sebagai gangguan pencernaan, khususnya dispepsia fungsional. Tujuan dari penelitian ini untuk mengetahui hubungan antara stres akademik dan kejadian dispepsia fungsional pada mahasiswa preklinik Fakultas Kedokteran Universitas Hang Tuah angkatan 2022. Penelitian ini menggunakan desain deskriptif korelasi dengan pendekatan cross-sectional. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah responden sebanyak 72 mahasiswa dari populasi angkatan 2022. Pengumpulan data dilakukan menggunakan PSS-10 untuk mengukur tingkat stres dan R4-FDDQ untuk diagnosis dispepsia fungsional. Analisis data dilakukan menggunakan uji statistik Chi-Square. Hasil penelitian menunjukkan bahwa terdapat hubungan yang bermakna antara stres akademik dengan dispepsia fungsional dari hasil uji Chi-Square dengan nilai p-value sebesar 0,014. Kesimpulan dari penelitian ini adalah terdapat hubungan yang signifikan antara stres akademik dan kejadian dispepsia fungsional pada mahasiswa preklinik Fakultas Kedokteran Universitas Hang Tuah angkatan 2022. Semakin tinggi tingkat stres akademik, semakin besar peluang terjadinya dispepsia fungsional.